Effect of a Bilingual Learning Multimedia Innovation Package on Vegetarian Dietary Practices Among Karen at Risk of Hypertension in Bann Phra bat Huai Tom, Lamphun Province - Katkanta, Chananchida; Aungwattana, Sivaporn; Tuanrat, Wilawan (Nursing Journal CMU, 2024)
Assessing health information enables individuals to learn and apply that knowledge to maintain good health. A bilingual learning multimedia innovation for Karen people, who are unable to communicate in Thai or only communicate in Thai to a limited extent, will help this population access health information. This quasi-experimental study used a two-group pretest-posttest design aiming to compare the vegetarian dietary practices of a group that received an innovative bilingual multimedia set before and after the experiment and to compare the vegetarian dietary practices between an experimental group and a control group over a 4-week period.The participants included 40 Karen people at risk of hypertension living in Bann Phra Bat Huai Tom, Lee district, Lamphun province, selected by purposive sampling, with 20 persons in the control group and 20 persons in the experimental group. The research instrument was a bilingual multimedia innovation regarding the practice of vegetarian cuisine consumption for Karen people at risk of hypertension, developed by the researcher from a product innovation concept and consisting of a bilingual education handbook (Thai-Karen language), a voice clip in Karen, bilingual still image media (Thai-Karen language), and a language test that was developed using the back translation principle by a general practice nurse who is bilingual. The content validity index of the questionnaire on the practice of vegetarian cuisine consumption was .9, and the Cronbach’s alpha coefficient was .81. Descriptive statistics were used for data analysis and included paired t-test and independent t-test. The study results indicated that, for the experimental group, the mean posttest score (M = 71.25, SD = 8.95) was higher than that of the mean pretest score (M = 57.23, SD = 6.87), and higher than that of the control group (M = 60.0, SD = 9.12) with statistical significance (p < .05). The results show that the bilingual learning multimedia innovation can be integrated to educate Karen people with hypertension to learn, leading to the practice of vegetarian food consumption according to the principles and ways of the community.